EVALUASI KADAR KALSIUM DAN FOSFOR PADA SAPI NON-LAKTASI DAN SAPI LAKTASI DI WILAYAH NGLIPAR GUNUNGKIDUL - , SETIAWAN REZKI INDARTA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Calcium and phosphorus are essential macrominerals and hold such an important role in physiological processes in animals. This study was conducted to evaluate calcium and phosphorus on lactation beef cattle in Nglipar, Gunungkidul. Ten beef cattles were involved in this study, which divided into 5 non-lactating and 5 lactating cows. As much as 5 mL blood were taken from jugular vein as the sample. All blood samples were centrifuged at 8000 rpm for 10 min. Calcium and phosphorus serum were analyzed using Cobas Â® c 501, Roche Diagnostics Ltd., Switzerland. Result from serum calcium analyzed on non-lactating and lactating cows were normal 10,22 + 0,28 mg/dl and 10,20 + 1,02 mg/dl. Phorsporus serum level in non-lactating cows 3,54 + 0,74 mg/dl and lactating cows was 6,06 + 1,06 mg/dl. There was no significant difference on serum calcium of non-lactating and lactating cows (P<0,05), meanwhile serum phosphorus there was significant difference between non-lactating cow and lactating cow. Based on the result of this study, it was concluded that non-lactating cows occur hypofosfatemia with ratio Ca : P (2,4-2,8 : 1).